Application of Remote Sensing and GIS in Droughts and Floods Assessment and Monitoring - Huang, Yaohuan; Liu, Yesen; Shi, Runhe; Ren, Hongyan (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This Special Issue collates seven papers regarding the assessment or monitoring of hydrological disasters such as droughts and flood using remote sensing and geography information system (GIS) techniques.. The new published research focused on evaluations and models of various hydrological hazards such as droughts and floods. Furthermore, we include two original scientific articles addressing the subject of water quality. This Special Issue received investigations based on different techniques such as remote sensing, GIS, machine learning and monitoring. All papers present findings characterized as unconventional, provocative, innovative and methodologically new. Scientific findings presented in this Special Issue highlight how a combination of various modern analysis techniques (e.g., remote sensing, GIS) can improve our understanding of complex hydrological hazards such as droughts and floods. We hope that the research contained within this Special Issue is useful to the scientific community, policymakers and stakeholders at large in the field of hydrological hazards.